2016
DOI: 10.1099/jmm.0.000228
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm formation of Brazilian meticillin-resistant Staphylococcus aureus strains: prevalence of biofilm determinants and clonal profiles

Abstract: Biofilms plays an important role in medical-device-related infections. This study aimed to determine the factors that influence adherence and biofilm production, as well as the relationship between strong biofilm production and genetic determinants in clinical isolates of meticillin-resistant Staphylococcus aureus (MRSA). Fifteen strains carrying different chromosomal cassettes recovered from hospitalized patients were selected; five SCCmecII, five SCCmecIII and five SCCmecIV. The SCCmec type, agr group and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 61 publications
1
14
0
1
Order By: Relevance
“…Furthermore, we found that the biofilm formation ability of MRSA isolates correlated with SCC mec types. Our results are consistent with a previous study showing that SCC mec type III‐harboring strains showed a significantly higher ability to form biofilms compared with the strains harboring SCC mec type IV; however, no difference in biofilm formation with type II‐positive isolates was observed after 4 and 24 hr of incubation, which differs from the literature (William da Fonseca Batistao et al, ). The multidrug‐resistant SCC mec type III isolates produced significantly stronger biofilms than types IV and V suggesting that biofilm formation in MRSA isolates plays a role in antibiotic resistance in the hospital setting.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that the biofilm formation ability of MRSA isolates correlated with SCC mec types. Our results are consistent with a previous study showing that SCC mec type III‐harboring strains showed a significantly higher ability to form biofilms compared with the strains harboring SCC mec type IV; however, no difference in biofilm formation with type II‐positive isolates was observed after 4 and 24 hr of incubation, which differs from the literature (William da Fonseca Batistao et al, ). The multidrug‐resistant SCC mec type III isolates produced significantly stronger biofilms than types IV and V suggesting that biofilm formation in MRSA isolates plays a role in antibiotic resistance in the hospital setting.…”
Section: Discussionmentioning
confidence: 99%
“…Caio Fernando de Oliveira [1] , Jorunn Pauline Cavanagh [2], [3] , Elizabeth G. Aarag Fredheim [2], [3] , Keli Cristine Reiter [4] , Alexandre Rieger [5] , Claus Klingenberg [3] , Pedro Alves d'Azevedo [4] and Johanna Ericson Sollid [6] [1]. Programa de Pós Graduação em Promoção da Saúde, Universidade de Santa Cruz do Sul, Santa Cruz do Sul, Rio Grande do Sul, Brasil.…”
Section: Coagulase-negative Staphylococci In Southern Brazil: Lookingunclassified
“…Laboratório de Biotecnologia e Genética, Universidade de Santa Cruz do Sul, Santa Cruz do Sul, Rio Grande do Sul, Brasil. [6]. Research Group for Host-Microbe Interactions, Department of Medical Biology, Faculty of Health Sciences, UiT-The Artic University of Norway, Tromsø, Norway.…”
Section: Coagulase-negative Staphylococci In Southern Brazil: Lookingmentioning
confidence: 99%
See 2 more Smart Citations